Biology, diagnostics, pathogenomics and mitigation strategies of jackfruit-bronzing bacterium Pantoea stewartii subspecies stewartii: what do we know so far about this culprit? - Ibrahim, Rohaya; Ismail, Siti Izera; Md Yasin, Ina-Salwany; Zulperi, Dzarifah (MDPI, 2022)
Jackfruit-bronzing disease, caused by Pantoea stewartii subsp. stewartii, has recently become more common in the jackfruit crop. Jackfruit-bronzing disease was first discovered in the Philippines in 2014 and spread to Malaysia and Mexico in 2017. Outbreaks of the disease reduced the quality of fresh jackfruit, lowered the market value of local jackfruit, and caused yield losses to the production and financial setbacks to the processors. This disease is more aggressive toward jackfruits with a sweeter flavor and high Brix composition. Symptoms are observable when the fruit is cut open, indicated by the appearance of rusty specks and yellowish-orange to reddish discoloration of the infected pulps and rags. Extensive research is needed to better understand the pathogen’s nature and pathogenicity, supporting future disease prevention and recognition of the pathogen-host interaction. This review explores the significance of the jackfruit-bronzing bacterium, its biology, diagnostics, and pathogenomics, emphasizing the pathogen’s virulence and the management strategies to mitigate this disease. Understanding this destructive bacterium will guide growers and agricultural practitioners to develop the most efficient and sustainable jackfruit-bronzing control methods.